2018
DOI: 10.1007/s11109-018-9445-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Preference in Mexican Migrants: Evidence from a Random Household Survey

Abstract: Does pre-existing preference based on skin tone, facial features, and other observable characteristics, i.e., phenotypic preference, affect immigrant voters' support for political candidates competing in their countries of origin? Do these preferences change as migrants's tenure in their host society increases? These question are important for ethnic and racial politics in general, and particularly for the sizable foreign-born population in the United States, which includes 11 million Mexicans. Using a unique,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…First, research on U.S. voter turnout suggests that political participation is higher among immigrants less exposed to discrimination (Schildkraut, 2005b) and groups that are more educated (Sondheimer & Green, 2010; Verba, Schlozman, & Brady, 1995); thus, because lighter-skinned Latinx women are more educated (Hunter, 2002) and less exposed to discrimination (Uzogara, 2019a), they may be more inclined to participate in the political process although this possibility has not been examined in this understudied literature. Second, lighter-skinned Latinxs may be favored as political candidates by long-term Mexican residents in the United States (Aguilar et al, 2019). Future research should examine the possibility that the lightest-skinned Latinx women may be more electable political candidates because the present study’s findings suggest that this group may not necessarily support legislation that corresponds with the policy preferences and interests of their darker-skinned Latinx constituents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, research on U.S. voter turnout suggests that political participation is higher among immigrants less exposed to discrimination (Schildkraut, 2005b) and groups that are more educated (Sondheimer & Green, 2010; Verba, Schlozman, & Brady, 1995); thus, because lighter-skinned Latinx women are more educated (Hunter, 2002) and less exposed to discrimination (Uzogara, 2019a), they may be more inclined to participate in the political process although this possibility has not been examined in this understudied literature. Second, lighter-skinned Latinxs may be favored as political candidates by long-term Mexican residents in the United States (Aguilar et al, 2019). Future research should examine the possibility that the lightest-skinned Latinx women may be more electable political candidates because the present study’s findings suggest that this group may not necessarily support legislation that corresponds with the policy preferences and interests of their darker-skinned Latinx constituents.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, skin tone has been more tied to political behaviors rather than political attitudes . Experimental studies found that light-skinned African Americans (Caruso, Mead, & Balcetis, 2009; Terkildsen, 1993; Weaver, 2012) and lighter-skinned Mexicans (Aguilar, Hughes, & Gell-Redman, 2019) were favored as political candidates in hypothetical and actual elections.…”
Section: Colonialism Colorism and Politicsmentioning
confidence: 99%
“…The levels of party identification were selected to show the most relevant parties in each country, based on data from the most recent wave of the AmericasBarometer at the time of the experiment . Ethnicity was included as an attribute in the Mexican survey because it is a relevant social cleavage (e.g., Aguilar et al 2019) and could thus impact how Mexicans view or perceive others with respect to themselves. Following Hainmueller et al 2013, the order of the attributes was randomized at the respondent level and kept fixed across all pairings for each respondent to minimize primacy and recency effects.…”
Section: Notesmentioning
confidence: 99%
“…In addition, such voters might receive a large amount of information that is difficult to filter, verify, or remember accurately (Olivola and Todorov, 2010….). Given the complexity of the voting process, voters have to use mental shortcuts to make their final decisions (Aguilar, Hughes, and Gell‐Redman, 2019; Gigerenzer and Gaissmaier, 2011; Lau and Redlawsk, 2001).…”
Section: Skin Tone and Electoral Politicsmentioning
confidence: 99%